(untitled) (Revista Apotheke, 2025)
This paper analyzes how the concept of experience permeates John Dewey’s philosophy, influencing studies on aesthetics, ethics, logic, politics and education, among other human sciences. In addition to this general intent, specific objectives are presented, such as describing the function and relevance of symbols for pragmatic philosophy and the educational context; reflecting on the aesthetic nature of experience and reasoned thought, in the face of the problems of existence; analyzing the nullification of the student’s desire for learning, due to traditional pedagogical knowledge that perpetuate the separation between theory and practice, among other procedures that do not consider experience; reflecting on evaluation, in the light of Deweyan pedagogical assumptions. As theoretical contributions, in addition to the author’s well-known works, such as Como pensamos (Dewey, 1959a), Democracia e Educação (1959b), Reconstrução em Filosofia (1959c), Logic: The Theory of Inquiry (1980), and Arte como experiência (2010), writings by Barbosa (2015), Cunha (1999), Shook (2002), Gauthier & Tardif (2010), among others, contribute to the reflective path. The methodological perspective is inspired by the concepts of Rorty’s redescription (1995). The reflection undertaken on the nature of experience, as enunciated by Dewey can shed light on the old scourge of students’ disinterest in educational routines.